Dual electronic-ionic conductivity of pseudo-capacitive filler enables high volumetric capacitance from dense graphene micro-particles. (June 2017) - Xu, Yue; Tao, Ying; Li, Huan; Zhang, Chen; Liu, Donghai; Qi, Changsheng; Luo, Jiayan; Kang, Feiyu; Yang, Quan-Hong
Abstract: Volumetric performance is highly important for evaluating the potential of supercapacitors, especially for the case where electrode space is limited. To achieve high space utilization, the less pores to be included the better. Along this direction, we showed previously a PANI/graphene composite almost free of porosity by shrinking the composite network to the most compact, which yet exhibited a high volumetric capacitance and a good rate capability. The PANI/graphene solid composite simultaneously enabled maximized space utilization of the electrode volume and achieved unimpeded ion transport, which seems counter to the general design principle of electrode materials where appropriate porous structure is highly desired. Here we propose the proton transport mechanism of PANI in the dense composite, which indicates that PANI is a dual electronic-ionic conductivity polymer that acts not only as a pseudo-capacitive active material for high energy storage but also as a proton conductor that realizes proton transport from the electrode/electrolyte interface to the inner of the dense micro-particles. More importantly, we further propose the design principle of non-porous carbon-based composites to achieve high volumetric performance, in which a good dual electronic-ionic conductor is selected as the best pseudo-capacitive filler. This work inspires new insights into better design and preparation of the composite electrodes for compact energy storage devices. Graphical abstract: The design principle of a graphene-based composite electrode material is proposed to achieve the maximum space utilization and superhigh volumetric capacitance, in which a pseudocapacitive filler with a good dual electronic-ionic conductor is required. Highlights: The design principle is proposed for a graphene-based composite electrode material achieving a high volumetric performance. A pseudocapacitive filler with dual electronic-ionic conductivity is required for a dense graphene composite electrode. PANI as a typical pseudocapacitive filler helps realize proton transport inside a porosity-free graphene micro-particle.